Current state of populations of useful plants of Almaty region and ways of their balanced use - Aidarbaeva, D.K.; Sholpankulova, G.A.; Shokanova, A.Sh. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the article the results of the study of the current state of useful plants in Almaty region are summarized. The study covered the territory of the Karasaz rural district. A modern assessment of the species diversity of the flora was given, the list of which according to the field survey data was 194 species belonging to 132 genera and 44 families. In the number of species among families Asteraceae Dumort was dominating — 33 species, Poaceae Juzz — 28 species, Fabaceae Lindl — 16 species, Labiatae Juss — 13 species, Rosaceae Juss — 11 species, Chenopodiaceae Vent — 12 species, Ranunculaceae Juss — 8 species, Liliaceae Juss — 6 species, Cyperaceae Juss, Iridaceae Lindl, Papaveraceae Juss — 5 species each; Brassicaceae Juss — 4 species, Cynomoriaceae Engl and Plantaginaceae Lindl — 3 species each, other 19 species were dominant according to vegetation cover. Distribution of more than 26 species of medicinal and 56 species of fodder plants were revealed. The predominant life form was represented by perennials — 172 species, of which long-growing perennial grasses made up — 148 species, shrubs — 14 species, semishrubs — 3 species each, shrubs and trees — 2 species each. The vast number of species is eaten by cattle and often mowed for hay, so a complete inventory and assessment of the current state of useful plants, development of recommendations for the conservation and restoration of their natural populations is relevant to the present day.
Алматы облысының пайдалы өсімдіктері популяциясының қазіргі жағдайы жəне оларды үйлестіріп қолдану жолдары
Современное состояние популяций полезных растений Алматинской области и пути их сбалансированного использования
Keywords: useful plants; forage plants; medicinal plants; flora; population; dominants; perennial grasses; shrubs; semi-shrubs